Kualitas Pakan Ikan Berbentuk Pelet Dari Pengolahan Limbah Ikan - Destalenta Trisna Laoli (Jurnal Ilmu Pertanian dan Perikanan, 2026)
Commercial fish feed is generally relatively expensive, thus necessitating the development of alternative feed sources based on locally abundant, affordable, and easily accessible raw materials, such as fish waste from traditional markets. This study aims to evaluate the quality of fish feed pellets produced from the processing of fish waste as an economical, environmentally friendly, and sustainable alternative to support the management of aquatic resources. The research was conducted on April 8, 2026, at the Laboratory of the Faculty of Science and Technology, Nias University, utilizing a quantitative descriptive methodology. The pellet manufacturing process involved washing, boiling, drying, and grinding fish waste into flour, which was then mixed with rice bran, soybean pulp, tapioca flour as a binder, fish vitamins, and water until homogeneous, before being molded and dried. The results demonstrated that the resulting pellets possessed favorable physical characteristics: cylindrical shape, grayish-brown coloration, dense texture, a distinctive fish aroma that was not rancid, moderate buoyancy lasting 2–4 minutes, and stability in water for approximately 30 minutes. These characteristics indicate that fish waste has the potential to be utilized as a raw material for feed, capable of enhancing feed efficiency while simultaneously reducing nutrient loss in cultivation media. Furthermore, converting fish waste into pellets adds value to fishery by-products, mitigates environmental pollution, lowers production costs, and supports the implementation of circular and blue economy principles in aquatic resource management. Consequently, fish waste-based pellets have the potential to serve as a high-quality, cost-effective, and sustainable local alternative, fostering increased productivity in aquaculture and the effective management of aquatic resources in Indonesia.